Pendampingan Sandur Sedhet Srepet di Jetak Bojonegoro dengan Strategi Pengembangan Produk Karya Pertunjukan - pramono, koko hari; lestari, lilis; putri, ratna mestikasari; firdaus, mujib (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
Traditional arts have challenges in preserving in the future, this is due to developments in information and technology which underlie the inheritance of traditional theater arts which need adjustments in order to remain sustainable. This important point in community service certainly makes it a service that has bargaining value for the people of Kalianyar Village, Kapas District, Bojonegoro Regency to become an option and strategy for developing research so that it can be carried out and become an understanding of the identity and inheritance of traditional theater. In this community service activity, the author created a sub-theme with research material on traditional arts using the four D (4D) development research model. In this article on community service, the author chooses the development method of S. Thiagarajan, Dorty S, Semmel, and Melvyn I. Where in R&D the Four-D development model consists of four stages, namely: Define, Design, Develop. ), Disseminate. Of these 4 stages of development, Sandur in Graffito by Oky Dwi Wicahyono will be described